2015
DOI: 10.3109/03009742.2014.982701
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of giant cell arteritis in Olmsted County, Minnesota, over a 60-year period 1950–2009

Abstract: Objective To assess the incidence of giant cell arteritis (GCA) in the current era (2000-2009). Methods We extended the previously identified population-based cohort of Olmsted County, MN residents who fulfill 1990 ACR criteria for GCA (1950-1999) for another decade. Results In 2000-2009, 74 cases of GCA were identified (mean age: 78.1 years; 80% women; 79% temporal artery biopsy positive; 7 included based on radiological criteria). The incidence of GCA was 19.8 per 100,000 population. Conclusions The GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 11 publications
6
60
0
1
Order By: Relevance
“…Prior studies have indicated an annual incidence of GCA of 19.8 per 100,000. 29,30 Assuming 8.2–48.8% of these patients suffer permanent vision loss, 85% from A-ION as discussed above, the annual incidence of A-ION from GCA of 1.3 per 100,000 in the current study is likely closer to the actual incidence of this complication. The higher incidence in the current study may also reflect the population of Olmsted County, which is 90.3% Caucasian according to the 2000 US census data.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Prior studies have indicated an annual incidence of GCA of 19.8 per 100,000. 29,30 Assuming 8.2–48.8% of these patients suffer permanent vision loss, 85% from A-ION as discussed above, the annual incidence of A-ION from GCA of 1.3 per 100,000 in the current study is likely closer to the actual incidence of this complication. The higher incidence in the current study may also reflect the population of Olmsted County, which is 90.3% Caucasian according to the 2000 US census data.…”
Section: Discussionmentioning
confidence: 50%
“…22,29,30,33,34 Interesting, Johnson and Arnold found no sex predilection for A-ION in their incidence study. 28 …”
Section: Discussionmentioning
confidence: 87%
“…(6, 14) The diagnosis was based on 1990 American College of Rheumatology criteria for classification of GCA. (15) Patients aged ≥50 years with elevation of erythrocyte sedimentation rate (ESR) or C-reactive protein (CRP) and computed tomography/angiography, magnetic resonance arteriography or positron emission tomography evidence of large vessel vasculitis involving the ascending aorta and/or its branches were also included.…”
Section: Methodsmentioning
confidence: 99%
“…The GCA cohort consisted of patients who fulfilled the 1990 ACR criteria for GCA in 1950–2009. [9, 10]. …”
Section: Methodsmentioning
confidence: 99%